A Randomized Single-Blinded Trial of VeraCept, a Novel Nitinol Low-Dose Copper Intrauterine Contraceptive Compared With a Copper T380S Intrauterine Contraceptive [16]. (May 2015) - Reeves, Matthew F.; Hathaway, Mark J.; Canela Oleaga, Juan M.; Katz, Bob H.; Tal, Michael G.
Abstract : INTRODUCTION: We aimed to compare VeraCept, a novel low-profile nitinol intrauterine contraceptive with 175 mm 2 of copper surface area, with a commercially available copper T380S. METHODS: We performed a randomized subject-blinded comparison of VeraCept and a copper T380S in a two-to-one fashion. The primary outcome was total continuation. We also examined pain on insertion, ease of placement, expulsion, satisfaction, tolerability, and pregnancy. Satisfaction ratings were on a 5-point Likert scale. We report data from insertion through 9-month follow-up. RESULTS: We enrolled women in a single clinic with 199 allocated to VeraCept and 101 to the T380S. Insertion was successful in 198 women for VeraCept and 100 for the T380S ( P >.2). Mean age was 25 years, and median parity was two (range 1–4) with 39% having only had cesarean deliveries. No women developed clinical infection or reported serious adverse events. In the VeraCept and T380S groups, mean pain at insertion was 1.4 and 2.4, respectively ( P <.01). At the 9-month visit for VeraCept and T380S, respectively, continuation was 86% and 70% ( P =.004) with partial and complete expulsions in 5.0% and 12.0% ( P <.05) and removal for pain or bleeding in 3.5% and 13.0% ( P <.05). No pregnancies were diagnosed after insertion with 1, 562 and 643 women-months for VeraCept and T380S, respectively. One "luteal phase" pregnancy was identified at the first follow-up with conception estimated at 1–1.5 weeks before VeraCept insertion. CONCLUSION: VeraCept resulted in less pain at insertion, fewer expulsions, and higher total continuation than the T380S with equal contraceptive efficacy to date.